Interrelationships among skeletal age, growth status and motor performances in female athletes 10-15 years - Duarte Freitas; António Antunes; Martine Thomis; Ricardo Silva; Gonçalo Marques; Alípio Silva; Rui Nunes; Marcelo Delgado; Paulo Jardim; Rubina Xíxaro; Joana Silva; Francisco Fernandes; et al. (Taylor & Francis Group, 2024)
AbstractBackground Motor performances of youth are related to growth and maturity status, among other factors.Aim To estimate the contribution of skeletal maturity status per se to the motor performances of female athletes aged 10-15 years and the mediation effects of growth status on the relationships.Subjects and methods Skeletal age (TW3 RUS SA), body size, proportions, estimated fat-free mass (FFM), motor performances, training history and participation motivation were assessed in 80 non-skeletally mature female participants in several sports. Hierarchical and regression-based statistical mediation analyses were used.Results SA per se explained a maximum of 1.8% and 5.8% of the variance in motor performances of athletes aged 10-12 and 13-15 years, respectively, over and above that explained by covariates. Body size, proportions, and hours per week of training and participation motivation explained, respectively, a maximum of 40.7%, 18.8%, and 22.6% of the variance in performances. Mediation analysis indicated specific indirect effects of SA through stature and body mass, alone or in conjunction with FFM on performances.Conclusion SA per se accounted for small and non-significant amounts of variance in several motor performances of female youth athletes; rather, SA influenced performances indirectly through effects on stature, body mass and estimated FFM.